Conceptual modelling and its theoretical foundations: Essays dedicated to bernhard thalheim on the occasion of his 60th birthday - Klettke, Meike; Schewe, Klaus-Dieter; Düsterhöft, Antje (Lecture Notes in Computer Science, 2012)
This Festschrift, published in honor of Bernhard Thalheim on the occasion of his 60th birthday presents 20 articles by colleagues from all over the world with whom Bernhard Thalheim had cooperation in various respects; also included is a scientific biography contributed by the volume editors. The 20 contributions reflect the breadth and the depth of the work of Bernhard Thalheim in conceptual modeling and database theory during his scientific career spanning more than 35 years of active research. In particular, ten articles are focusing on topics like database dependency theory, object-oriented databases, triggers, abstract state machines, database and information systems design, web semantics, and business processes.